The Impact of Maine’s Municipal Shellfish Management on Clam Harvester Motivation to Participate in Resource Conservation - Freer, Rachel; Bieluch, Karen; Cox, Michael (Maine Policy Review, 2025)
Over the last decade, landings from one of Maine’s most valuable marine resources, soft-shell clams, have declined due to environmental and social stressors. To address this challenge, some municipal shellfish committees have encouraged or required harvesters to participate in conservation activities, which are intended to help protect and grow the resource. However, harvester involvement varies, leaving resource managers wondering how they can increase participation. This study draws on interviews and a survey in four focal communities to examine harvester participation in conservation activities, their internal and external motivation to participate, and the factors that may influence those motivations. Findings indicate that conservation requirements and committees composed of harvesters are positively correlated to harvesters’ intrinsic motivation to participate in formal conservation activities. These insights may help municipal and state agencies refine future shellfish conservation policies and recommendations.
Keywords: clam harvesters; intrinsic motivation; extrinsic motivation; community science; comanagement